Immediate Repair of a Complete Uterine Transection After Motor Vehicle Collision. Issue 5 (November 2020) - Mankus, Erin; Braun, Andrew; Knudtson, Jennifer; Medrano-Valle, Gabriel; McCann, Georgia
Abstract : BACKGROUND: Traumatic separation of the cervix from the uterine corpus is rare. We describe a case in which this injury was identified and surgically repaired at initial presentation to preserve fertility. CASE: An 18-year-old woman presented with a pelvic crush injury after a motor vehicle accident. Imaging revealed pelvic fractures and bladder rupture. Complete transection of the uterine corpus at the level of the internal os was identified at laparotomy. The gynecology service was consulted and circumferentially reattached the corpus to the cervix. CONCLUSION: Uterine integrity should be confirmed in female patients with pelvic crush injuries who undergo exploratory laparotomy given the unknown extent of intra-abdominal trauma. Immediate surgical correction of uterine transection at the time of injury with restoration of the genital outflow tract is feasible and may allow preservation of fertility. Abstract : Fertility preservation is possible with immediate recognition and surgical anastomosis after complete traumatic separation of the uterine corpus from the cervix.